Isogeometric Analysis and Bayesian Optimization on Efficient Weld Geometry Design for Remarkable Stress Concentration Reduction. (October 2021) - Aung, Thein Lin; Ma, Ninshu
Abstract: Shape optimization combined with Isogeometric Analysis will be an efficient design method since exact Computer Aided Design geometries can be used for numerical analysis thanks to the same basis functions. In this study, authors developed an in-house research software JWRIAN-IGA and applied it to optimize the weld geometries of two models, namely a T-joint fillet weld and an elongated boxing fillet weld to reduce stress concentration. A gradient-free stochastic global optimization algorithm, Bayesian Optimization was used to sought optimal geometry parameters. It was shown that the optimized geometry was efficiently designed and the stress concentration in the welds for both cases was greatly reduced. Highlights: Integrated geometry-analysis-optimization framework was developed. Two weld geometries were optimized to reduce stress concentration. Multi-patch Isogeometric Analysis was utilized to analyze the weld models. Stochastic global optimization algorithm was used to find the optimal weld shapes.